2016
DOI: 10.1007/s00167-016-4326-4
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of post-operative devices following knee arthroscopic surgery: a systematic review

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 55 publications
1
31
1
5
Order By: Relevance
“…7) However, few studies have reported on its relationship with increased muscle strength. 8) Although the present study did not show an intergroup difference in pre-intervention MPQ, it showed a significant post-intervention decrease in MPQ in the Elex group, compared with the Tex group. However, there were no significant differences between the groups in terms of the post-intervention CS-30, which indicates quadriceps endurance, or TUG, which indicates balance ability.…”
Section: Discussioncontrasting
confidence: 86%
“…7) However, few studies have reported on its relationship with increased muscle strength. 8) Although the present study did not show an intergroup difference in pre-intervention MPQ, it showed a significant post-intervention decrease in MPQ in the Elex group, compared with the Tex group. However, there were no significant differences between the groups in terms of the post-intervention CS-30, which indicates quadriceps endurance, or TUG, which indicates balance ability.…”
Section: Discussioncontrasting
confidence: 86%
“…It is equal to the square root of the total power contained within the EMG signal. The ARV of the EMG signal calculates the mean of the rectified or absolute value 27 of the EMG signal amplitude, Figure 11B. The ARV is proportional to RMS of the EMG amplitude when the level of muscle activity is sufficiently high (83).…”
Section: Surface Emg Amplitude Features (Time Domain)mentioning
confidence: 99%
“…This channel could be displayed to the patient visually to target the lower trapezius (increase recruitment), which can become inhibited and limit full range of motion in shoulder abduction. In a similar way, the inclusion of EMG biofeedback in conventional exercise programs can facilitate recovery after surgery ( 26 , 27 ) and can also improve the effectiveness of training programs [e.g., pelvic floor muscle training ( 28 30 )]. Surface EMG biofeedback can also be useful in cases where muscular tension causes pain, as the visual stimulus can help the patient to relax or deactivate the muscles [e.g., alleviating neck ( 31 , 32 ) and low back pain ( 33 )], Figure 2B .…”
Section: Background and Applicationsmentioning
confidence: 99%
“…The use of neuromuscular electrical stimulation (NMES) is recommended to be utilized with all patients following ACL reconstruction. The results of a recent systematic review found NMES improves quadriceps isometric torque, quadriceps peak torque, isokinetic knee extension strength, and led to a faster recovery of quadriceps strength [20]. Stimulation can be performed in full knee extension for patients with bone-patella-bone grafts and at 60°isometrically for patients with allografts or hamstring autografts.…”
Section: Early Post-operative Complicationsmentioning
confidence: 99%